If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 = 0.5(6 + 4x) Reorder the terms: 3 + 2x = 0.5(6 + 4x) 3 + 2x = (6 * 0.5 + 4x * 0.5) 3 + 2x = (3 + 2x) Add '-3' to each side of the equation. 3 + -3 + 2x = 3 + -3 + 2x Combine like terms: 3 + -3 = 0 0 + 2x = 3 + -3 + 2x 2x = 3 + -3 + 2x Combine like terms: 3 + -3 = 0 2x = 0 + 2x 2x = 2x Add '-2x' to each side of the equation. 2x + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 0 = 2x + -2x Combine like terms: 2x + -2x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 1.8x+0.7=1.1x-1.4 | | (2)+(-5)= | | (2)=(-5) | | (3)+(1)= | | 2x2/3= | | 0.75x-1.37=0.42x-0.05 | | c/-.03=-5.1 | | 5-(x-3)=1/4(2x-4) | | p(x)=-2x^2-4x+6 | | 5/7q-3/10=4/5 | | 9-13z=12-6z-7 | | p(x)=0.7t^2+12t+400 | | 19x=361 | | 3x^2-28x-481=0 | | 3+x+2x=x+3 | | 5+4=2061 | | ln(2x+5)=4.7 | | (3u-7)=34 | | 6/7y-1/8=1/4 | | 50-3x=1008x | | 5x-11-2x=19-3x+10 | | -7n^2=8n+10 | | 6(n-3)+4n=92 | | (1/2)(1/6)= | | -7n^2-8n=10 | | -3(d-6)=-7d+-6 | | 5d+8+7d-1= | | (5*x^-8/8*y^-9)^-2 | | -7n^2-8n-10=0 | | 3y-4(1+3y)=9-5(y-2) | | (4z-1)=3(z+2) | | 12a+3+3a+2= |